'The lamentation of a vacuum cleaner': appliance disappointments in John Cheever and Richard Yates. Issue 7 (3rd July 2021) - Dini, Rachele
ABSTRACT: This article examines the depiction of domestic appliances in a selection of short stories by John Cheever (a man who famously feared and mistrusted all electrical appliances), and Richard Yates (the son of an alcoholic regional sales representative for General Electric). What I call Cheever and Yates's 'appliance disappointments' dismantle the idealised depictions of appliances in post-war television sitcoms (the majority of which were sponsored by the very same appliance brands that appeared in said sitcoms' storylines). I argue that these texts merit particular attention in light of recent developments in US studies that have shed light on the imbrication of television, consumer culture, and Cold War politics. While Cheever's malfunctioning appliances explicitly recall the explosive potential of the atomic bomb, Yates' shabby appliances throw into relief their owners' vanquished aspirations. Cheever and Yates's appliance narratives draw attention to both authors' acute awareness of the extent to which domestic life post-1945 revolved around gadgets (both televised and real) and their acknowledgement of such gadgets' status as veritable actors in the drama of particularly white middle-class domesticity.